Visualizing Empire: Cyprus and the Colonial Travelogue Film in the 1920s. Issue 5 (2nd September 2020) - Stubbs, Jonathan
ABSTRACT: This article examines the ways in which the British colonial government used cinema to represent Cyprus to audiences in Britain during the 1920s and early 1930s. The primary focus is the troubled production and exhibition history of the 1929 film Cyprus, but the article also considers the earlier production Cyprus Cinematograph Film (1924), plus two later sound films derived from material in the Cyprus film: Almost Arcady (1930) and A Mediterranean Island (1932). I argue that these films reflect the Cyprus government's filmmaking inexperience, as well as their difficulty in determining how best to showcase their colonial project to domestic audiences. As a result, the films reveal conflicting impulses in their representation of the island, soberly cataloguing the historical and geographical features of the island on the one hand, but also seeking to exoticise an unfamiliar environment and population for western consumption. The article concludes by comparing the filmmaking efforts of the Cyprus government with contemporaneous films produced by the Italian government in the nearby Dodecanese islands and by the British government through the Empire Marketing Board.